Hubungan Konformitas dengan Kepuasan Hidup pada Mahasiswa Pengguna Media Sosial Instagram di Yogyakarta - Kania Sabilla; Ratna Yunita Setiyani Subardjo (EduInovasi: Journal of Basic Educational Studies, 2024)
Individuals who have low life satisfaction tend to change their current situation, so they have a greater orientation to make changes to their lives, which triggers an individual to do conformity, which conformity itself is interpreted as the tendency tochange individual beliefs or behaviors to match the behavior of others. This study aims to find out whether there is a relationship between conformity and life satisfaction in students who use Instagram social media in Yogyakarta. The data collection method in this study uses two likert scales, namely: the life satisfaction scale and the conformity scale. The subject of this study is students who use Instagram social media in Yogyakarta with a vulnerable age of 17-24 years, the sample used a purposive sampling technique totaling 100 respondents. Based on the results of the study conducted with the Pearson product moment correlation technique, the significance figure p = 0.000 (p< 0.05) this shows a significant relationship between the variable of life satisfaction and conformity in students who use Instagram social media in Yogyakarta.